Magic tree house survival guide - Osborne, Mary Pope.; Boyce, Natalie Pope.; Murdocca, Sal (New York : Random House, 2014)
"Jack and Annie show readers how to survive their many thrilling adventures"--Provided by publisher.
4.0
3-6
Keywords: Survival -- Juvenile literature; Survival; Survival skills; JUVENILE NONFICTION / Adventure & Adventurers; JUVENILE NONFICTION / Science & Nature / Disasters; JUVENILE NONFICTION / Health & Daily Living / Safety; Survival